Implications for training in youth: Is specialization benefiting kids? - Sugimoto, D.; Stracciolini, A.; Dawkins, C. I.; Meehan, W. P.; Micheli, L. J. (Strength and Conditioning Journal, 2017)
Early sports specialization has been a controversial topic in the field of sports medicine, training, and conditioning. Recent studies report increased sports-related injuries in single-sport specialized athletes compared with multisport specialized athletes. Two studies demonstrate the proportions of athletes who focused on a single sport in early ages and advanced to elite level in their later careers are <1%. Furthermore, performing multiple sports was identified as an indicator for greater future athletic success. Synthesizing available evidence, participating in multiple sports seems more beneficial than focusing on a single sport. It is important to provide adequate recovery time for pediatric and adolescent athletes because they are in a growth spurt process. Finally, because a history of previous injury is evidenced as a risk factor for future sports-related injuries, preventive approaches such as resistance training need to be implemented within a training regimen for youth. Siehe auch: https://ylmsportscience.com/2017/04/09/implications-for-training-in-youth-is-specialization-benefiting-kids/